2014
DOI: 10.1042/bj20131432
|View full text |Cite
|
Sign up to set email alerts
|

Novel evidence for the specific interaction between cholesterol and α-haemolysin of Escherichia coli

Abstract: Several toxins that act on animal cells present different, but specific, interactions with cholesterol or sphingomyelin. In the present study we demonstrate that HlyA (α-haemolysin) of Escherichia coli interacts directly with cholesterol. We have recently reported that HlyA became associated with detergent-resistant membranes enriched in cholesterol and sphingomyelin; moreover, toxin oligomerization, and hence haemolytic activity, diminishes in cholesterol-depleted erythrocytes. Considering these results, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 29 publications
1
46
0
Order By: Relevance
“…They further showed that a peptide corresponding to CRAC336 inhibited the LtxA cytotoxic activity and demonstrated that a point mutation in the CRAC336 site abolished LtxA toxicity. The conservation of CRAC336 among RTX toxins suggests that this mechanism may be conserved among RTX toxins, and indeed a specific interaction between cholesterol and E. coli HlyA has recently been reported [381]. DiFranco et al [382] reported that binding of LtxA to LFA-1 results in the internalization of both LtxA and LFA-1.…”
Section: Interaction With Cell Receptors and Trafficmentioning
confidence: 96%
“…They further showed that a peptide corresponding to CRAC336 inhibited the LtxA cytotoxic activity and demonstrated that a point mutation in the CRAC336 site abolished LtxA toxicity. The conservation of CRAC336 among RTX toxins suggests that this mechanism may be conserved among RTX toxins, and indeed a specific interaction between cholesterol and E. coli HlyA has recently been reported [381]. DiFranco et al [382] reported that binding of LtxA to LFA-1 results in the internalization of both LtxA and LFA-1.…”
Section: Interaction With Cell Receptors and Trafficmentioning
confidence: 96%
“…The presence of cholesterol in the membrane was, indeed, previously found to enhance the binding and lytic capacity of CyaA on erythrocytes and artificial membranes 30 , 40 . Moreover, two other RTX toxins, the Aggregatibacter actinomycetemcomitans leukotoxin LtxA and the Escherichia coli α-hemolysin HlyA, were previously shown to specifically bind cholesterol 41 43 . These toxins possess in their pore-forming domains the so called cholesterol recognition/interaction amino acid consensus (CRAC) motifs.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of LtxA with its human host is multifaceted and involves both the membrane lipids (cholesterol; Brown et al, 2013) and a cell-surface glycoprotein lymphocyte function-associated antigen 1 (LFA-1), a β 2 integrin family member (Lally et al, 1997). LtxA contains a conserved cholesterol recognition amino acid consensus motif (Brown et al, 2013;Vazquez et al, 2014) that is defined by the sequence -L/V-X 1-5 -Y-X 1-5 -R/K- (Epand, 2006;Li, Yao, Degenhardt, Teper, & Papadopoulos, 2001). The presence of the binding sequence ( 334 LEEYSKR 339 ) enhances the maximal affinity (minimal K d ) of the toxin for membranes containing 40% cholesterol, which is approximately four orders of magnitude (10 −12 M) greater than the affinity for cholesterol-free membranes (10 −8 M).…”
mentioning
confidence: 99%
“…The KIM185 epitope (residues 581-621) is located at the distal end of CRR-4 and extends onto the stalk to a point 57 amino acids from the LFA-1 transmembrane segment (Lu et al, 2001). The ability of LtxA to bind cholesterol (Brown et al, 2013;Vazquez et al, 2014), interact with extra cellular domains of LFA-1 (Lally et al, 1997), and modify bilayer structure (Brown et al, 2012) suggests that the LtxA/LFA-1 interaction is not confined to the ectodomains of LFA-1 but rather is providing a clear pathway for LtxA to enter the cytosol.…”
mentioning
confidence: 99%